Kontribusi Cara Belajar Dan Media Pembelajaran Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Penggunaan Alat Ukur Elektronika Kelas X Teknik Audio Video Di SMK Negeri 1 Kecamatan Guguak Kabupaten 50 Kota - Miswardi Miswardi; Sukaya Sukaya; Yusri Abdul Hamid (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2014)
This research is purposed to reveal the contribution of learning and instructional media on learning outcomes in subjects use electronic measuring instrument class X Audio Video Techniques In SMK Negeri 1 Kecamatan Guguak Kabupaten 50 Kota . The research is a descriptive correlational . The research population numbered is 59 people and sample totaled 37 students of class X Audio Video Techniques In SMK Negeri 1 Kecamatan Guguak Kabupaten 50 Kota Academic Year 2012/2013 .Using Technique of random sampling ( Simple random sampling ) . and Data collection using questionnaires and documentation . Data were analyzed using Pearson product moment correlation and multiple correlation for analysis . The results of data analysis showed : 1 ) how to learn to contribute 19.82 % of the student learning outcomes , 2 ) Learning Media contributed 25.16 % to the student learning outcomes , 3 ) How to Learn and Learning Media jointly contributed 27.84 % of the student learning outcomes in subjects Use of Electronic Measurement Techniques class X Audio Video SMK Negeri 1 Kecamatan Guguak Kabupaten 50 Kota . The results of this study indicate that the learning and instructional media contribute to student learning outcomes .